Você está na página 1de 5

# AS FÓRMULAS COMEÇAM NO CIFRÃO DUPLO E TERMINA NO CIFRÃO

DUPLO

EXERCÍCIOS 1 (PÁG. 6)
1.
$$3\times6=18=\frac{36}{2}=\frac{1+1+\cdots +1+1}{2}$$

2.
$$\frac{\frac{2}{7}+\xi }{x-\frac{1}{\sigma }}$$

3.
$$\sum \omega\chi \rho \alpha \tau o\upsilon \varsigma\, foi\,um\,folosofo\,grego\,\,extremamente\,importante.$$

## EXERCÍCIOS 2 (PÁG. 11)

1.
$$\mathbb{N}\subset \mathbb{Z}\subset \mathbb{Q}\subset \mathbb{R}\subset \mathbb{C}$$

2.
$$\mathbb{C}\setminus \mathbb{R}\neq\varnothing$$
3.
$$\left ( f\circ g \right )\left ( x \right )=f\left ( g\left ( x \right ) \right ),\forall x\in X$$

4.
$$\left ( p\Rightarrow q \right )\Leftrightarrow \left ( \left ( \neg\,p \right )\vee q \right )$$

## EXERCÍCIOS 3 (PÁG. 15)

1.
$$x^{10-3}$$

2.
$$\widehat{f-g}\left ( x \right )\times\,h(\hat{y})$$

3.
$$\vec{F_{2^{n}-1}}-\vec{F_{2^{n-1}}}$$

4.
$$\underbrace{a+b+\overbrace{c+\cdots +x+y+z}^{23}}_{26}$$
EXERCICIOS 4 (pág. 22)
1.
$${f}'\left ( x_{0} \right )=\lim_{x\rightarrow x_{0}}\frac{f\left ( x \right )-f\left ( x_{0} \right )}{x-x_{0}}$$

2.
$$\zeta \left ( z \right )=\frac{\Gamma \left ( 1-z \right )}{2\pi i}\oint_{\gamma }\frac{u^{z-1}}{e^{-u}-1}du$$

3.
$$\gamma =\lim\left ( \sum_{j=1}^{n}\frac{1}{j}-\ln\,n \right )$$

4.
$$\sum_{j=1}^{\infty }\frac{1}{j^{x}}=\prod_{p\in \left \{ primos \right \}}\frac{1}{1-p^{- x}}$$

5.
$$\left ( K\oplus L\right )_{n}=\underset{p+q=n}{\bigoplus}K_{p}\oplus L_{q}$$

(Pág. 29)
QUESTÃO 1
$$\bar{R^{4}}\eta \bar{R}=\bigl(\begin{smallmatrix} 1 & 0\\ 1 & R^{4} \end{smallmatrix}\bigr)\bigl(\begin{smallmatrix} -1 &0 \\ 0&I \end{smallmatrix}\bigr)\bigl(\begin{smallmatrix} 1 &0 \\ 0&R \end{smallmatrix}\bigr)= \bigl(\begin{smallmatrix} -1 &0 \\ 0& I \end{smallmatrix}\bigr)=\eta$$

QUESTÃO 2
$$e^{uB3}=\sum_{n=0}^{+\infty }\frac{1}{n!}\left ( \frac{u}{2} \right )^{n}\begin{bmatrix} 1 & 0\\ 0 & -1 \end{bmatrix}^{n}=\begin{bmatrix} e^{\frac{u}{2}} & 0\\ 0& e^{\frac{-u}{2}} \end{bmatrix}\in SL\left ( 2,\mathbb{C} \right )$$

QUESTÃO 3
$$\left\{\begin{matrix} x{}'+\sigma x-\sigma y=0\\y{}'+\sigma x+u+xz=0 \\ z{}'+bz-xy=-b\left ( r+\sigma \right ) \end{matrix}\right.$$

QUESTÃO 4
$\begin{eqnarray*} A^{-\alpha }A^{-\beta }&=& \frac{1}{\Gamma \left ( \alpha \right )\Gamma \left ( \beta \right )}\int_{0}^{\infty }\int_{0}^{\infty }t^{\alpha -1}s^{\beta -1}e^{-A\left ( t+\alpha \right )}\\ &=&\frac{1}{\Gamma \left ( \alpha \right )\Gamma \left ( \beta \right )}\int_{0}^{\infty}e^{-Au}\left ( \int_{0}^{u}t^{\alpha -1\left ( u-t \right )^{\beta -1}dt} \right )du\\ &=&\frac{1}{\Gamma \left ( \alpha \right )\Gamma \left ( \beta \right )}\int_{0}^{\infty}u^{\alpha +\beta -1}e^{-Au}\left ( \int_{0}^{1}z^{\alpha - 1}\left ( 1-z \right )^{\beta -1}dz \right )du\\ &=&A^{-\left ( \alpha +\beta \right )} \end{eqnarray*}$